(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the article, it will be considered what is the influence of the addition of 10% PP into a polyethylene mixture compared to a mixture of polyethylene on the main mechanical characteristics of geocells - hardness, maximum tensile strength, strength of the internal structural junctions (welds). It will be analyzed the interrelationships between the measured mechanical parameters.